Innovative Science Textbook Development: Integrating Local Wisdom into the Basic Science Concepts Course for Pre-Service Teachers - Winangun, I Made Ari; Suma, Ketut; Subagia, I Wayan; Sudiatmika, A.A. Istri Agung Rai (Jurnal Pedagogi dan Pembelajaran, 2025)
The limitation of representative learning resources is still a challenge in organizing science learning in higher education. This study aims to analyze the characteristics, test the validity, and evaluate the practicality of case-based Basic Concepts of Elementary Science Series 1 (Physics) textbooks with the context of local wisdom. This research is a research and development (R&D) study using the ADDIE model. The research subjects consisted of 72 students, 8 experts, and 6 lecturers in the field of elementary science. Data were collected through interviews, questionnaires, and documentation at each stage of development. The instruments used included interview guidelines and questionnaires to identify characteristics, as well as assess the validity and practicality of the textbooks. Data analysis techniques were carried out descriptively qualitative and quantitative. The results showed that the textbook developed covered seven physics topics with a chapter structure consisting of an introduction, material preceded by local wisdom-based case studies, summaries, exercises, and reference lists. The coursebook was rated as highly valid from the content and cultural aspects (Aiken's V = 0.983) and language aspects (Aiken's V = 0.925). In addition, the practicality of the coursebook was rated very high by lecturers and students, with an average score of 4.448 and 4.300 respectively at the initial trial stage, as well as 4.805 and 4.348 at the main trial stage. The conclusion of this study confirms that the developed textbooks are valid and practical, and support contextualized and culturally responsive science learning. The implication of this research highlights the importance of integrating local wisdom in the development of science learning resources to increase relevance and learner engagement.